Ethics committees and the legality of research - Douglas, T (BMJ Publishing Group Ltd., 2007)
One role of research ethics committees (RECs) is to assess the ethics of proposed health research. In some countries, RECs are also instructed to assess its legality. However, in other countries they are explicitly instructed not to do so. In this paper, I defend the claim that public policy should instruct RECs not to assess the legality of proposed research ("the Claim"). I initially defend a presumption in favour of the Claim, citing reasons for making research institutions solely responsible for assessing the legality of their own research. I then consider three arguments against the Claim which may over-ride this presumption - namely, that policy should instruct RECs to assess the legality of research because (1) doing so would minimise the costs of assessing the legality of research, (2) whether research is legal may partly determine whether it is ethical and (3) whether research is legal may constitute evidence for whether it is ethical. I reject the first two arguments and note that whether the third succeeds depends on the answer to a more fundamental question about the appropriate nature of REC ethical deliberation. I end with a brief discussion of this question, tentatively concluding that the thid argument also fails.